Spatio-temporal movement of water and nitrate under different dripper discharges in drip fertigation - KUMAR, MUKESH; RAJPUT, T B S; PATEL, NEELAM (The Indian Journal of Agricultural Sciences, 2016)
Fertigation is an advanced and efficient method of application of nutrients with irrigation water to the crop. Water and nutrient distribution in soil is one of the most important parameters to design efficient fertigation system. A field research was conducted to investigate the effect of dripper discharge at different system operating pressures on spatio-temporal soil moisture movement. The value of moisture contents varied significantly (P<0.05) under different operating pressures (0.5, 1.0 and 1.5 kg/cm2) and at different locations below and away from the dripper. Highest values of soil moisture contents were observed below the drippers which decreased as the distance increased in both horizontal and vertical directions from the dripper. The values of moisture content in soil decreased as distance increase in both directions (horizontal and vertical) from the dripper. 9.4% and 14.3% higher values of soil moisture just below the dripper were observed with dripper discharges of 1.41 and 1.71 l/hr at 1.0 and 1.5 kg/cm2 system operating pressures as compared to 0.94 l/hr dripper discharge at 0.5 kg/cm2 system operating pressure. Wetting front extended up to 15, 20 and 26 cm horizontally and 30, 30 and 24 cm and extended vertically up to 0.94, 1.41 and 1.71 l/h dripper discharge at 0.5, 1.0 and 1.5 kg/cm2 system operating pressure, respectively after 1 day of irrigation. Higher values of NO3-N concentration in all soil depths were recorded at 1.5 kg/cm2 operating pressure however lower values of NO3-N concentration were recorded at 0.5 kg/cm2 operating pressure 1 day after fertigation.